Analisa kualitas air sumur bor Jalan Bulutangkis Kota Malang berdasarkan parameter fisika dan parameter kimia - Azizah, Nur (Maliki Interdisciplinary Journal, 2024)
Water is an important natural resource for every life. Water that meets physical parameters is water that is odorless, colorless, and tasteless. Water that meets chemical parameters is water that does not contain toxic substances. This research is a type of laboratory descriptive research. The results showed that the analysis of the quality of borehole water was based on the water quality standards set by the government, namely PERMENKES NO 492/MENKES/PER/IV/2010 which met the requirements as a good source of drinking water and clean water for use